KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENULIS TEKS DESKRIPSI MENGGUNAKAN MEDIA VIDEO PENGETAHUAN ALAM KELAS VII SMP - Siti Aisah Batubara (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This research was conducted to find out the influence of natural knowledge video media on students' critical thinking skills in writing the text of the description of class VII junior high school student Siman Jaya Lamongan. This type of research uses Quasi experiment (pseudo experiment), pretest- posttest control group design design. Data collection techniques in the form of giving assignments to write description text to students. Data analysis techniques are carried out using prerequisite tests in the form of normality tests and homogenite tests, after which hypothesis tests are conducted using t-tests with a significant level of 5% (0.05). The results found in this study were that students' critical thinking ability to write text descriptions in control classes had an average score of 69.65 while in the experimental class had an average score of 79.81. Based on the hypothesis test using the t-test shows that the value of thitung = 5.40, thus it is known if thitung > ttabel i.e. (5.40 > 2.004) then Ho is rejected and Ha is accepted. Based on this, it can be concluded that there is a significant influence on students' critical thinking skills in writing description texts using media in the form of natural knowledge videos in class VII siman jaya lamongan junior high school.